Mengintegrasikan Automasi pada Perpustakaan SMPN 10 Jakarta: Studi Kasus Implementasi SLiMS di Era Society 5.0 - Yasmin, Anisa Putri; Abidin, Saenal; Umar, Touku (Inkunabula: Journal of Library Science and Islamic Information, 2024)
This study aims to analyze the implementation of library automation at SMPN 10 Jakarta in the Society 5.0 era using the Senayan Library Management System (SLiMS). A qualitative research method with a case study approach was employed, involving direct observation and semi-structured interviews with librarians and the head librarian of SMPN 10 Jakarta. Observations were conducted during two visits in March 2024. The results indicate that the implementation of SLiMS enhanced the library’s operational efficiency, particularly in collection management and circulation service quality. The increased speed and accuracy of circulation transactions contributed to improved user satisfaction. Enhanced information accessibility through the Online Public Access Catalog (OPAC) facilitated user autonomy in information retrieval. Primary challenges included technical constraints and limited librarian understanding, which were addressed through intensive training and ongoing support. In conclusion, the application of library automation at SMPN 10 Jakarta has positively impacted the teaching-learning process and students’ literacy development, aligning with the demands of the Society 5.0 era. This research contributes to the development of an automation implementation model that can be adapted by other school libraries in Indonesia. Abstrak Penelitian ini bertujuan untuk menganalisis implementasi automasi perpustakaan pada SMPN 10 Jakarta di Era Society 5.0 menggunakan Senayan Library Management System (SLiMS). Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus, melibatkan observasi langsung dan wawancara semi-terstruktur dengan pustakawan dan kepala pustakawan SMPN 10 Jakarta. Observasi dilakukan dalam dua kunjungan pada bulan Maret 2024. Hasil penelitian menunjukkan bahwa implementasi SLiMS meningkatkan efisiensi operasional perpustakaan, terutama dalam pengelolaan koleksi dan kualitas layanan sirkulasi. Peningkatan kecepatan dan akurasi transaksi sirkulasi berkontribusi pada peningkatan kepuasan pengguna. Peningkatan aksesibilitas informasi melalui OPAC memfasilitasi kemandirian pengguna dalam penelusuran informasi. Tantangan utama meliputi kendala teknis dan keterbatasan pemahaman pustakawan, yang diatasi melalui pelatihan intensif dan pendampingan berkelanjutan. Kesimpulannya, penerapan automasi perpustakaan di SMPN 10 Jakarta memberikan dampak positif pada proses belajar-mengajar dan pengembangan literasi siswa, sejalan dengan tuntutan era Society 5.0. Penelitian ini berkontribusi pada pengembangan model implementasi automasi yang dapat diadaptasi oleh perpustakaan sekolah lain di Indonesia.